Formação superior de professores em serviço e práticas pedagógicas: análise da efetividade das políticas da primeira década do século XXI no estado do Acre - Grace Gotelip Cabral (2010)
This theory analyzes the public policies of in-service teachers' formation, conceived and implemented in the state of Acre , especially, in the first decade of the XXI century. A panoramic view is presented regarding the governmental initiatives in the formulation and implementation of educational policies, and among them, one denominated as Special Programs for the Teachers Formation from the Basic Education PEFPEB (in PT-BR), with distinction for the Special Program of Teachers Formation from the Elementary Education and Initial Years of the Fundamental School in the Modular Course of Pedagogy. The research was guided by the following problem: what repercussions and/or changes were carried out by the referred program, as public policies for in-service formation in the college level, regarding to the pedagogical practice quality of the teachers who finished the course. It was developed with 150 teachers of the beginning years of the Fundamental School of the public system of Education in Rio Branco AC, and involved 10 pedagogical coordinators. It is a qualitative research, of explanatory descriptive nature, in a case study framework. The collection of data had involved field work and had as methodological procedures the application questionnaire, interviews and documental analysis. The adopted theoretical background was underpinned principally by the academic production of Evangelista, Shiroma and Moraes (2002), Mainardes (2006) and Bello (2008), concerning the discussion and analysis of the formulation of public policies; Schön (1982), Zeichner (1983) and Zeichner and Liston (1997), with the supporting discussions by Santos (2007) and Nóvoa (1991,1995), referring to the formation patterns; and Mizukami (2002), Libâneo (1998, 2004), Zabala (1998), Tardif (1991, 1999, 2000), Gauthier (1998), Pimenta (1999, 2002), Hadji (2001), Perrenoud (1999, 2000) and Guimarães and Marin (1998), with reference to the discussions on the pedagogical practices and knowledge, and the teacher's competences. The results of the research reveal the repercussions, the changes and the maintained pedagogic practices attributed by the subjects of the research to the initial formation found at in-service college level; the gaps left by the formative process and their implications in the daily school life; and the relationships among formulation and implementation of the teachers' formation policies, its effectiveness and the education quality rates reached by the State of Acre.